Credits - Conservación, Ge (Ge-conservacion, 2017)
Editorship: Rocío Bruquetas Galán. Editorial Board: María Aguiar, Emilio Cano Díaz, Rafael Fort González, Emma García Alonso, Silvia García Fernández-Villa, Marisa Gómez González, Ana Laborde Marqueze. Editorial Board of the YOCOCU 2016´ Special Issue: Monica Alvarez de Buergo, Miguel Gomez-Heras, Mauro La Russa and Andrea Macchia. Editing Secretary: Mª Concepción de Frutos Sanz. GEIIC Webmaster: Oscar Muñoz Lozano and Mª Concepción de Frutos Sanz Layout: Mª Concepción de Frutos Sanz Cover image: Logotype designed by Laura López-González for the 5th international conference Youth in Conservation of Cultural Heritage YOCOCU 2016, held at MNCARS (Madrid), from 21st to 23rd September 2016.